2000
DOI: 10.1086/315330
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Interferon‐γ Signaling byLeishmania donovani

Abstract: Leishmania infection causes marked down-regulation of interferon (IFN)-gamma-induced gene activity in macrophages, but the mechanism of the blockade has not been fully defined. The IFN-gamma signal transduction pathway was analyzed in Leishmania donovani-infected phorbol-differentiated U937 human promonocytic cells. IFN-gamma stimulation induced marked phosphorylation of its own receptor (IFN-gammaR)-alpha chain. Phosphorylation of the receptor subunit was significantly inhibited after 24 h of infection with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 44 publications
7
63
0
Order By: Relevance
“…After incubation at 371C for the 18 h, noningested parasites were removed by vigorous washing with RPMI three times. The infected macrophages were treated with 2.5 mM CPT and 0.2% DMSO separately for 12 h. 49 …”
Section: Culture Differentiation and Infection Of U937 Cellsmentioning
confidence: 99%
“…After incubation at 371C for the 18 h, noningested parasites were removed by vigorous washing with RPMI three times. The infected macrophages were treated with 2.5 mM CPT and 0.2% DMSO separately for 12 h. 49 …”
Section: Culture Differentiation and Infection Of U937 Cellsmentioning
confidence: 99%
“…A few reports have shown that infection results in expression of fewer IFNγ receptors on the infected cell surface and reduced phosphorylation of the remaining receptors ( Fig. 1) (Nandan and Reiner, 1995;Ray et al, 2000). Using mice genetically altered to lack SHP-1, Olivier and colleagues have shown that activation of this phosphatase during infection blocks Jak2 signaling (Blanchette et al, 1999;Forget et al, 2001).…”
Section: Suppression Of Nitric Oxide Productionmentioning
confidence: 99%
“…IL-12 induces the differentiation and proliferation of CD4 + Th1 cells populations, which produce more IFN-γ (Cunningham 2002). IFN-γ is responsible for activating macrophages to produce TNF-α, which, in synergism with IFN-γ, increases phagocytosis and induces macrophage leishmanicidal activity through the production of nitrogen and oxygen metabolites (Belosevic et al 1989, Bodgan et al 1990, Liew et al 1990, Theodos et al 1991, Ray et al 2000, Wilhelm et al 2001, Cunningham 2002. On the other hand, susceptibility to leishmaniasis is associated with a Th2 type immune response, characterised by the predominance of the humoral response and the production of cytokines, such as IL-4 and IL-10 ( Agnello et al 2003, Sharma & Singh 2009.…”
mentioning
confidence: 99%